Comparative performance of lab tests and blood testing device to monitor glucose, total cholesterol and triacylglycerol in type 2 diabetic patients - Arnaldo Zubioli; Marcia Regina Batista; Talitha Fernandes Stefanello; Marcia Aparecida Carrara; Roberto Barbosa Bazotte (Universidade de São Paulo, 2011)
The performance of lab tests (LT) and blood testing devices (BTD) to monitor glycemia vs. glycated hemoglobin A1c (A1c) were compared. In addition, the performance of blood glucose, total cholesterol (TC) and triacylglycerol measured by LT and BDT were compared. All parameters were measured based on the same blood samples from overnight fasted type 2 diabetic patients (T2DP). Linear regression analysis was used for all comparisons. The results showed that A1c correlated better with LT-glucose (r = 0.58) than BTD-glucose (r = 0.42). Moreover, LT vs. BTD showed r values of 0.90, 0.82 and 0.92 for glucose, TC and triacylglycerol, respectively. It was concluded that the performance of LT-glucose was better than BDT-glucose. Moreover, since triacylycerol and TC measured by BTD correlated better with LT compared to BDT-glucose vs. LT-glucose, the inclusion of BTD-TC and BTD-triacylglycerol for detecting and monitoring hyperlipidemia in T2DP should be considered. Comparou-se a performance de avaliação da glicemia através de dosagens laboratoriais (DL) ou dispositivo para teste de sangue capilar (DTSC) vs. hemoglobina glicada A1c (A1c). Comparou-se ainda a performance de avaliação da glicemia, colesterol total (CT) e triacilglicerol (DL vs. DTSC). Avaliou-se estes parametros a partir das mesmas amostras de sangue coletadas em pacientes diabéticos tipo 2 (PDT2) em jejum noturno, sendo as comparações realizadas através de análise de regressão linear. A A1c correlacionou-se melhor com a glicemia-DL (r = 0,58) em relação a glicemia-DTSC (r = 0,42). Comparou-se DL vs. DTSC obtendo se r = 0,90, 0,82 e 0,92 para glicemia, CT e triacilglicerol, respectivamente. Concluiu-se que houve melhor performance da glicose-DL em relação a glicose-DTSC. Além disso, considerando que o triacilglicerol e TC avaliado através de DTSC correlaciona-se melhor com DL em comparação a DTSC-glicose vs. DL-glicose, a inclusão de DTSC-TC e DTSC-triacilglicerol visando detectar e monitorar hyperlipidemia in PDT2 deve ser considerada.